TINJAUAN HUKUM PEMISAHAN (SPIN OFF) UNIT USAHA SYARIAH MENJADI PERUSAHAAN ASURANSI SYARIAH (FULL FLEDGE) - Nursania Dasopang (Institut agama islam negeri Padangsidimpuan, 2019)
Islamic insurance versus conventional insurance has fundamental differences. Although Islamic insurance starts from one unit of a conventional company as its parent. As a separate unit, sharia offers products that are certainly different from conventional insurance and based on sharia provisions. Where to avoid the practice of gharar, maisir, and usury. For this reason, it is necessary to separate the sharia insurance business unit into a Sharia Insurance Company (Full Flegde). With the aim of increasing insurance growth more rapidly. Spin-off prospects of Sharia Insurance Companies include: Insurance development is considered to be more competitive, improve the quality of trust and image, improve the quality of trust and image, increase productivity and efficiency, improve capital structure, provide benefits to policyholders and shareholders, support public trust in Islamic insurance.